If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -62 = s Reorder the terms: -62 + 3s = s Solving -62 + 3s = s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1s' to each side of the equation. -62 + 3s + -1s = s + -1s Combine like terms: 3s + -1s = 2s -62 + 2s = s + -1s Combine like terms: s + -1s = 0 -62 + 2s = 0 Add '62' to each side of the equation. -62 + 62 + 2s = 0 + 62 Combine like terms: -62 + 62 = 0 0 + 2s = 0 + 62 2s = 0 + 62 Combine like terms: 0 + 62 = 62 2s = 62 Divide each side by '2'. s = 31 Simplifying s = 31
| 5p-60=p-4 | | n-8-1=-13 | | -5-7k+8k=0 | | x=2x-70 | | -12a-5b=27 | | 3z=z+26 | | r/320 | | 4n-2n+4=1+17 | | 4v-3+8=13 | | -1/2w-7/5=4/3 | | 3+3(2-6)squared= | | -8a-2a=-10 | | b+4=2b-3 | | -x-8=x+2 | | -4(5x-4)+3(4x+2)= | | 6n-3=3n-15 | | 2(2x+2)-3(x-4)= | | A/2=36 | | 84=78+n | | -x+7x=-12 | | -x^2+5=(4x-1)(4x-1) | | 4a+7a=7a+16 | | v/-4=13 | | -0.25+0.6= | | -0.25-0.6= | | (13m-11)=2m+5 | | -6(b-6)+4=88 | | 4.5s-s= | | 0.25-0.6= | | x*3+75=x*9-9 | | 18x11/(18x11)= | | 13m-11=2m+5 |